Mnemonics Strategies and its Effects on English Vocabulary Building on Sixth Grade Students in Mafraq Educational Directorate - a Case Study – - Al-khaza'aleh, Ala'a Odtallah (Journal of Educational and Psychological Sciences, 2020)
This case study examined the effect of mnemonic strategies on improving sixth grade students’ English vocabulary building. This study examined into students’ response and their point of view toward using mnemonic strategies in teaching English vocabularies. A chick list was built based on experts’ notes and English language teachers’ observations in Mafraq educational directorate, Jordan, during 2019-2020 the first academic semester and vocabulary lessons were conducted using mnemonic strategies depending on the curricula to examine the validity and reliability of the research tool. Data from the teacher’s observation was analyzed and the results showed the highest mean range was stated as ’’Students make a mental map for a familiar place in their minds’’ with mean range (20). And the lowest mean range was stated as ’’ Students decode words by numbers throughout giving each consonant sound a number’’ with mean range (5). Based on the results of the study the researcher recommends using mnemonic strategies to improve students’ English vocabulary building.